The influence of cold, warm and hot deformation on microstructure and mechanical properties of Inconel 718 superalloy - Doğan, Tugay; Gündüz, Süleyman; Taştemür, Demet (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This study systematically examines the influence of precipitation on the microstructural and mechanical properties of Inconel 718 superalloy in as-received, solution heat-treated, peak-aged, and overaged conditions. Cold, warm, and hot deformation tests were performed at 25 °C, 400 °C and 800 °C using a constant strain rate of 5.55 × 10⁻⁴ s⁻¹. The results indicated dynamic strain aging during warm deformation at 400 °C in all investigated conditions. However, at temperatures above 400 °C, a pronounced reduction in strength was observed, accompanied by a corresponding increase in elongation for most conditions. Notably, the solution heat-treated samples exhibited anomalous behavior, showing an increase in Rp0.2 after deformation at 800 °C. This suggests the occurrence of dynamic precipitation during hot deformation in the solution heat-treated samples.
Keywords: Super alloys; Dynamic strain ageing; Microstructure; Mechanical properties